Faktor determinan risiko kardiometabolik pada remaja usia 15-18 tahun - Wiboworini, Budiyanti; Shabrina, Amalina; Dewi, Yulia Lanti Retno; Sari, Amelya Augusthina Ayu; Handayani, Sutartinah Sri; Damayanti, Kusmadewi Eka; Azzahrah, Aisyah; Tjung, Vivienne (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2024)
Determinant factors of cardiometabolic risk in adolescents aged 15-18 yearsBackground: Cardiometabolic diseases are increasing worldwide, and the risk of developing them starts as early as adolescence. In the long term, they may lead to comorbidities. Evidence suggests the risk factors of cardiometabolic diseases among adolescents are obesity, excessive food intake, socioeconomic status, breakfast habits, and physical activity, among others. Objective: This study aimed to determine the determinants of cardiometabolic risk in adolescents aged 15-18. Methods: This was a cross-sectional study in Al-Abidin High School Surakarta with 146 study subjects. Cardiometabolic risks were classified using Cardiometabolic Disease Staging (CMDS), waist circumference was measured with Medline, physical activity was measured using a Physical Activity Questionnaire for Adolescents (PAQA), and blood pressure was measured with a sphygmomanometer. Socioeconomic, transportation, and breakfast habits were obtained from the general questionnaire. Chi-square, ANOVA, and logistic regression were then performed using SPSS 23. Results: Gender was significantly associated with cardiometabolic risk (p=0.001). A total of 41.3% of boys were at risk of cardiometabolic (OR=3.964). Socioeconomic, breakfast habits, transportation, and physical activity were not associated with cardiometabolic risk (p>0.05).Conclusion: Boys 15 – 18 years were at a higher risk of cardiometabolic, by 3.694 times greater than girls. Socioeconomic status, breakfast habits, transportation, and physical activity were not correlated with cardiometabolic risk among adolescents.